Effectiveness of Biological Therapy in Psoriasis: Real-World Evaluation of SII and SIRI as Biomarkers of Systemic Inflammation - Bardazzi, Federico; Rapparini, Luca; Paolini, Arianna; De Benedetto, Giorgio; Loi, Camilla; Lenzi, Jacopo; Piraccini, Bianca Maria; Clarizio, Giacomo (Dermatology Practical & Conceptual, 2026)
Introduction: Psoriasis is a chronic inflammatory skin disease characterized by accelerated keratinocyte turnover and systemic inflammation mediated by an altered immune response. Biological drugs have significantly improved treatment outcomes in moderate to severe psoriasis. The Systemic Inflammation Response Index (SIRI) and the Systemic Immune-Inflammation Index (SII) have emerged as potential biomarkers for assessing systemic inflammation.Objective: The primary objective of this study was to assess changes in SIRI and SII over six and 12 months across different biological therapies (TNF-α, IL-17, IL-12/23, and IL-23 inhibitors) in patients with moderate-to-severe psoriasis. Secondary objectives included evaluating the impact of sex and comorbidities (obesity, metabolic syndrome, or psoriatic arthritis) on inflammatory markers reduction.Methods: A retrospective observational single-center study was conducted analyzing records from January 2010 to December 2024. Patients with moderate-to-severe psoriasis (PASI >10) and at least one comorbidity were included. The study excluded those with other chronic inflammatory diseases or immunosuppressive treatment.Results: Among 98 patients, TNF-α and IL-17 inhibitors showed the greatest SII reduction, while TNF-α and IL-12/23 inhibitors had the most significant SIRI reduction. Males exhibited a greater reduction in both indices. Among comorbidities, obesity was associated with the most pronounced decrease in inflammatory indices, followed by metabolic syndrome and psoriatic arthritis, which showed significant but less marked reductions.Conclusions: SII and SIRI may serve as valuable biomarkers for monitoring systemic inflammation in psoriasis patients undergoing biological therapy. Further studies are needed to validate their role in routine disease management.